Physico - chemical treatment of Bukit Tagar sanitary landfill leachate using P-Floc775 and Ferric chloride - P., Agamuthu; Al – Abdali, Said Nasser Ali (Malaysian Journal of Science, 2009)
Bukit Tagar Sanitary landfill leachate was characterized and then treated with ferric chloride and P-Floc775, individually. The raw leachate contained high concentration of BOD5 ( 27000 mg/L), COD ( 59000 mg/L ), NH3-N (4300 mg/L ), Pb (15.15 mg/L), Al (15.75 mg/L ), Zn (17.55 mg/L ), Fe (84.3 mg/L ), Cu (10.95 mg/L), Cd (11.25 mg/L) and As (3.6 mg/L). All these parameters exceeded the Malaysian regulatory standard limit of EQA 1974 (Standard A and B). Leachate treatment was optimum with 2g/500ml FeCl3 at pH 7 and mixing speed 100 rpm. It was able to reduce about 100% of Cd, Pb and Cu to below the Environmental Quality (Sewage and Industrial Effluent) Regulation Standard B while Zn was reduced by 89% but was still above standard B. The optimum for P-Floc775 was 2ml/500ml, pH7 and mixing speed 90 rpm. Maximum removal of Cd and Cu was 100% which was below the Environmental Quality Regulation Standard B requirements. P-Floc775 was able to reduce Pb and Zn by 82% and 88%, respectively, which were still above Standard B. Further integrated leachate treatment is recommended to achieve the EQA regulation limits. Ciri-ciri larut lesapan dari tapak pelupusan sanitari Bukit Tagar telah dikaji dan dirawat dengan ferric klorida dan P-Floc775 secara berasingan. Larut lesapan mentah tersebut mengandungi kepekatan yang tinggi untuk BOD5 (27000 mg/L), COD (59000 mg/L), NH3-N (4300 mg/L), Pb (15.15 mg/L), Al (15.75 mg/L), Zn (17.55 mg/L), Fe (84.3 mg/L), Cu (10.95 mg/L), Cd (11.25 mg/L) dan As (3.6 mg/L). Semua parameter tersebut melebihi tahap piawai Malaysia (EQA’ 1974, Standard A dan B). Rawatan larut lesapan adalah optimum dengan 2g/500ml FeCL3 pada pH 7 dan kelajuan campuran 100 rpm. FeCl3 dapat mengurangkan sebanyak 100% Cd, Pb dan Cu sehingga di bawah Piawai B, Akta Kualiti Alam Sekitar (Kumbahan dan Buangan Industri). Sementara Zn dapat dikurangkan sebanyak 89% tetapi masih melebihi Piawai B. Optimum untuk P-Floc775 adalah 2ml/500ml, pH 7 dan kelajuan campuran 90 rpm. Tahap maksima penyingkiran Cd dan Cu adalah 100% di mana ia adalah di bawah keperluan Pengawalan Piawai B, Kualiti Alam Sekitar. P-Floc775 masing-masing dapat mengurangkan Pb dan Zn sebanyak 82% dan 88%, di mana ia masih melebihi Piawai B. Rawatan larut lesapan sepadu selanjutnya dicadangkan untuk mencapai linkungan piawai pengawalan EQA.